The pesticide index - Copping, L. G.; Kidd, H; Tomlin, C D S (British Crop Protection Council, 1995)
This book is an easy-to-access reference source for the active ingredients and tradenames of pesticides currently available worldwide. It provides information on components, activity and marketing companies of most pesticides likely to be encountered.